PENERAPAN PROGRAM BIMBINGAN DAN KONSELING BERBASIS PREVENTIF TERHADAP PENURUNAN PROBLEMATIKA REMAJA BAGI ANAK BERHADAPAN DENGAN HUKUM DI UPT PRSMP SURABAYA - Lestari, Murni; Bambang Dibyo Wiyono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Children in conflict with the law (ABH) represent a complex social phenomenon requiring holistic rehabilitation interventions. This study aims to evaluate the effectiveness of a preventive-based guidance and counseling program in reducing adolescent problems among ABH at UPT Perlindungan dan Rehabilitasi Sosial Marsudi Putra (PRSMP) Surabaya. A quasi-experimental design with a one-group pre-test post-test approach was employed, involving 30 male participants aged 15–17 years. Data were collected using an Adolescent Problem Scale consisting of 21 items covering five dimensions: aggressive behavior and juvenile delinquency, self-understanding and self-control, social and family relationships, psychological conditions, and life motivation and goals. Data analysis used the Paired Sample T-Test after normality was confirmed through the Shapiro-Wilk test. Results showed a significant decrease in mean scores from pre-test (M = 63.90, SD = 5.641) to post-test (M = 39.77, SD = 4.477), with t(29) = 93.901, p = 0.000 (p < 0.05). The most notable reduction was in the aggressive behavior dimension (Δ = 6.36), while self-understanding, social relationships, and life motivation showed positive improvements. These findings confirm that a structured, preventive-based guidance and counseling program is statistically effective in reducing adolescent problems among ABH and contributes to the development of evidence-based social rehabilitation interventions in Indonesia.